SARS-CoV-2 Neutralizing Human Antibodies Protect Against Lower Respiratory Tract Disease in a Hamster Model. (8th June 2021) - Haagmans, Bart L; Noack, Danny; Okba, Nisreen M A; Li, Wentao; Wang, Chunyan; Bestebroer, Theo; de Vries, Rory; Herfst, Sander; de Meulder, Dennis; Verveer, Elwin; van Run, Peter; Lamers, Mart M; et al.
Abstract: Effective clinical intervention strategies for coronavirus disease 2019 (COVID-19) are urgently needed. Although several clinical trials have evaluated use of convalescent plasma containing virus-neutralizing antibodies, levels of neutralizing antibodies are usually not assessed and the effectiveness has not been proven. We show that hamsters treated prophylactically with a 1:2560 titer of human convalescent plasma or a 1:5260 titer of monoclonal antibody were protected against weight loss, had a significant reduction of virus replication in the lungs, and showed reduced pneumonia. Interestingly, this protective effect was lost with a titer of 1:320 of convalescent plasma. These data highlight the importance of screening plasma donors for high levels of neutralizing antibodies. Our data show that prophylactic administration of high levels of neutralizing antibody, either monoclonal or from convalescent plasma, prevent severe SARS-CoV-2 pneumonia in a hamster model, and could be used as an alternative or complementary to other antiviral treatments for COVID-19. Abstract : Prophylactic treatment with a highly neutralizing mAb or convalescent plasma protects against SARS-CoV-2 infection in the lower but not upper respiratory tract.